Health, Safety, Incentives And Motivation In Employee Performance At Aneka Lovina Villas & Spa - Juli Nuryani, Ni Nyoman (Technium Social Sciences Journal, 2021)
This study aims to determine the effect of health & safety on motivation, the effect of incentives on motivation, the effect of health & safety on employee performance, the effect of incentives on employee performance, the effect of motivation on employee performance at Aneka Lovina Villas & Spa. This study uses a quantitative approach, the population in this study are all employees of various lovina villas & spas. The sample was 79 respondents who were determined by questions in the form of a questionnaire to the respondents. The technique uses saturated samples. The data analysis technique used in this research is the SPSS model. The results showed that health & safety had a positive and significant effect on motivation, incentives had a positive and significant effect on motivation, health & safety had a positive and significant effect on employee performance, incentives had a positive and significant impact on employee performance, and motivation had a positive and significant effect on performance. employee.